Reflections from One Latino Field: Notes from Research Among Central Americans in the United States - Cecilia Menjívar (Cahiers des Amériques Latines)
Based on more than a decade of research in Central American immigrant communities in different US cities, I share reflections about my interactions with study participants in the different communities I have studied. I recount how my multiple social characteristics, experiences, and trajectories have deeply affected the dynamics of such interactions. Paradoxically, those same characteristics that might facilitate access to a particular individual or groups can simultaneously hinder data collection among the same group. Highlighting differences and similarities between my study participants and myself, I argue that far from being a detached observer, the qualitative researcher is engaged in the act of conducting research, and thus, personal characteristics of both the researcher and the researched shape the nature of the data gathered, the analysis, and ultimately what is written.